Deskripsi Keterampilan Bertanya Guru Pada Pembelajaran Tematik Kelas III SD Negeri 13 Pontianak Barat - Iqlimah Iqlimah; Kartono Kartono; Rio Pranata (Departement of Mathematics Education, 2023)
This study aims to determine the ability of basic questioning skills and advanced questioning skills of third grade teachers of SD Negeri 13 West Pontianak. The sub-problems in this study are how is the teacher's ability to apply basic questioning skills in thematic learning? How is the teacher's ability to apply advanced questioning skills in thematic learning? And what is the impact of the application of teacher questioning skills on student learning outcomes in thematic learning. The research method used is descriptive with a qualitative research form. The data sources of this research were teachers and students of class III B of SD Negeri 13 West Pontianak. Data collection instruments in this study were researchers, observation sheets, and documentation. Data analysis in this study used an interactive model with the stages of data reduction, data presentation, and conclusion drawing. The results of the research on the application of basic questioning skills of class III B teachers of SD Negeri 13 West Pontianak, namely from 6 components of basic questioning skills, only 5 components are well implemented, there is 1 component whose indicators have not been implemented, namely the question redirection component. While the application of advanced questioning skills of class III B teachers of SD Negeri 13 West Pontianak from 4 components of advanced questioning skills has been well implemented, but there is 1 component that has not been mastered, namely the tracer question component.